Extispicy in the Everyday: An Art Project-in-Progress - Couch, Amanda (Cuizine)

(untitled) (McGill University Library, 2018)
Extispicy in the Everyday is a project-in-progress which explores the continued fascination with innards in the human imagination, particularly reinterpreting extispicy, the ancient practice of divination using the entrails.